1999
DOI: 10.1006/viro.1999.9791
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Visualization of Tegument/Capsid Interactions in the Intact Human Cytomegalovirus

Abstract: The three-dimensional structure of the intact human cytomegalovirus (HCMV) was determined to 18-A resolution by electron cryomicroscopy and computer reconstruction. Its capsid shell is composed of pentons, hexons, and triplexes arranged on a T = 16 icosahedral lattice and is identical to that of the B-capsid isolated from host cell nuclei. An icosahedrally ordered tegument layer formed by 960 copies of filamentous density is also visualized, which interacts with the pentons, hexons, and triplexes of the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 16 publications
4
126
0
1
Order By: Relevance
“…Our results showed that the MHV-68 capsid structure is highly similar to those reported for HSV-1 and cytomegalovirus (Butcher et al 1998;Chen et al 1999;Trus et al 1999;, members of the alphaherpesvirus and betaherpesvirus subfamilies, respectively. This is consistent with mass spectrometry results showing that the MHV-68 capsid consists of proteins that are highly homologous to capsid proteins of other herpesviruses (Bortz et al 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed that the MHV-68 capsid structure is highly similar to those reported for HSV-1 and cytomegalovirus (Butcher et al 1998;Chen et al 1999;Trus et al 1999;, members of the alphaherpesvirus and betaherpesvirus subfamilies, respectively. This is consistent with mass spectrometry results showing that the MHV-68 capsid consists of proteins that are highly homologous to capsid proteins of other herpesviruses (Bortz et al 2003).…”
Section: Discussionsupporting
confidence: 87%
“…HCMV (AD169 and Towne strain) and HFFs were obtained from American Tissue Culture Collection (ATCC; Rockville, Maryland) and Clonetics Inc+ (San Diego, California), respectively+ The HFFs were maintained and propagated in DMEM supplemented with 10% fetal bovine serum+ HSV-1 (F), a prototype of human herpes simplex virus 1, was a gift from Dr+ Bernard Roizman of the University of Chicago+ The anti-IE72 monoclonal antibody, mAb1203, and a mixture of anti-HCMV glycoprotein B (gB) neutralizing monoclonal antibodies (nAb), mAb1204, 1206, and 1212, were obtained from Goodwin Cancer Research Institute (Plantation, Florida; Navarro et al+, 1993)+ The monoclonal antibody against gH was purchased from Biodesign Inc+ (Kennebunk, Maine)+ HFFs were infected with HCMV and the viral particles were purified by double tartrate glycerol ultracentrifugation procedures (Irmiere & Gibson, 1985;Chen et al+, 1999)+ The infectivity of the purified HCMV was evaluated by titering the particles in HFFs and the intactness of their structures was examined first by obtaining negative staining images with a conventional transmission electron microscope (University of California-Berkeley Electron Microscopy Core Facility) and further confirmed by electron cryomicroscopy (Chen et al+, 1999)+ In vitro selection procedure Double-stranded DNA templates were synthesized by PCR using oligonucleotide JH101 (59-GCCGGATCCGGGCCTC ATGTCGAANNNNNNNNNNNNNNNNNNNNNNNNNNNNN NNNNNNNNNNNTTGACCGTTTATTCTTGTCTCC-39) as the template+ JH101 contained a randomized sequence indicated as (N) 40 and underlined+ The 59 and 39 PCR primers were oligodeoxynucleotides JH1031 (59-CCGAAGCTTAAT ACGACTCACTATAGGGAGACAAGAATAAACGGTCAA-39) and JH1052 (59-CCCTCATGTCGAA-39), respectively+ JH1031 also contained the promoter sequence for bacteriophage T7 RNA polymerase+ Transcription reactions were carried out in 40 mM Tris-HCl, pH 7+9, 6 mM MgCl 2 , 10 mM DTT, 2 mM spermidine, 0+5 mM each of ATP and GTP, and 1 mM each of 29 amino-UTP and 29 amino-CTP (Amersham Inc+, Arlington Heights, Illinois) in the presence of a-[…”
Section: Viruses Cells and Antibodiesmentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) is a ubiquitous herpes virus that causes mild or subclinical diseases in immunocompetent adults but may lead to severe morbidity or mortality in neonates and immunocompromised individuals (Britt & Alford, 1996;Mocarski, 1996)+ Infection by this virus accounts for one of the most common opportunistic diseases (i+e+, CMV retinitis) encountered by AIDS patients+ Very few effective drugs (e+g+, ganciclovir) are currently available and the emergence of drug-resistant strains of HCMV has created a need for the development of new drugs and novel treatment strategies (Jacobson et al+, 1991;Palestine et al+, 1991)+ In vitro selection or SELEX (systematic evolution of ligands by exponential enrichment) procedures (Ellington & Szostak, 1990;Tuerk & Gold, 1990;Joyce, 1992) have been used to isolate oligonucleotide molecules (aptamers) with high affinity to a wide variety of lowmolecular-weight targets and large complexes such as red blood cell membranes (Ellington & Szostak, 1992;Gold et al+, 1995Gold et al+, , 1997Pan et al+, 1995;Morris et al+, 1998;Yang et al+, 1998;Homann & Goringer, 1999)+ This approach has also been used to select RNA aptamers to bind to Rous sarcoma virus (RSV) and African trypanosome, and RNA ligands that inhibited RSV infection were isolated (Pan et al+, 1995;Homann & Goringer, 1999)+ In these procedures, single-stranded oligonucleotide molecules that exhibited the highest affinity to a target were selected from a pool of randomized sequences by reiterative cycles of selection and amplification+ In this study, we employed a modified in vitro selection procedure to isolate ribonucleaseresistant RNA ligands that tightly bind to HCMV infectious particles+ The selected ligands exhibited high HCMV-binding affinity in vitro and effectively inhibited viral infection in tissue culture+ Two of the ligands appeared to block viral entry by interacting with viral surface glycoproteins+ Our study demonstrates the feasibility of using these RNA ligands as a research tool to identify HCMV proteins essential for infectivity and as an antiviral agent to block HCMV infection+ rimidine nucleotides, selection experiments in vitro for the modified RNA molecules that bind to infectious HCMV, and purification and amplification of the selected sequences+ The viral particles were isolated from HCMV-infected human foreskin fibroblasts (HFFs) by gradient ultracentrifugation as described previously (Irmiere & Gibson, 1985;Chen et al+, 1999)+ The infectivity of the purified HCMV was evaluated by titering the particles in human fibroblasts and the intactness of their structures was examined first by obtaining negative staining ima...…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, preformed viral capsids are packaged with genomic DNA and have to be transported to the cytoplasm for final maturation and viral release. Due to the large size of cytomegaloviral capsids (~130 nm; Chen et al, 1999), these cannot be transported through the nuclear pore complex (~40 nm; PantĂ© & Kann, 2002). The most widely accepted model for nuclear egress of HCMV and other herpesviruses is based on a transient primary envelopment by budding through the inner nuclear membrane (Mettenleiter, 2004(Mettenleiter, , 2006Sanchez & Spector, 2002;Sampaio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%